2019
DOI: 10.1093/nar/gkz271
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific CRISPR–Cas9 activation by microRNA-dependent expression of anti-CRISPR proteins

Abstract: The rapid development of CRISPR–Cas technologies brought a personalized and targeted treatment of genetic disorders into closer reach. To render CRISPR-based therapies precise and safe, strategies to confine the activity of Cas(9) to selected cells and tissues are highly desired. Here, we developed a cell type-specific Cas-ON switch based on miRNA-regulated expression of anti-CRISPR (Acr) proteins. We inserted target sites for miR-122 or miR-1, which are abundant specifically in liver and cardiac muscle cells,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 89 publications
2
58
0
2
Order By: Relevance
“…AAV plasmids were generated via restriction enzyme cloning, all other constructs were cloned by Golden Gate assembly (50). The vector for co-expression of NmeCas9 and the VEGFA sgRNA was previously published by us (51). All other sgRNAs were cloned into plasmid pEJS654 All-in-One AAV-sgRNA-hNmeCas9 (kind gift from Erik Sontheimer, Addgene plasmid #112139) via the SapI restriction sites.…”
Section: General Methods and Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…AAV plasmids were generated via restriction enzyme cloning, all other constructs were cloned by Golden Gate assembly (50). The vector for co-expression of NmeCas9 and the VEGFA sgRNA was previously published by us (51). All other sgRNAs were cloned into plasmid pEJS654 All-in-One AAV-sgRNA-hNmeCas9 (kind gift from Erik Sontheimer, Addgene plasmid #112139) via the SapI restriction sites.…”
Section: General Methods and Cloningmentioning
confidence: 99%
“…The dual luciferase reporter was previously reported by us (49). AcrIIC3-LOV2 hybrid constructs were created by inserting the LOV2 domain into our published CMV-driven AcrIIC3 expression vector (Addgene plasmid #120301) (51). To this end, the AcrIIC3 vector was linearized by an around-the-horn PCR using primers carrying BbsI restriction sites as 5' extension.…”
Section: General Methods and Cloningmentioning
confidence: 99%
“…Moreover, Acrs can be harnessed to enable the temperatureresponsive [41] and optogenetic [42] control of CRISPR-Cas activity. Importantly, Acrs can enhance the editing [38] and cell-type [43] specificities and reduce the cytotoxicity [11] of CRISPR-Cas-mediated genome editing. It has also been reported that Acrs can facilitate the production of CRISPR-carrying viral vectors by restricting CRISPR selfcleavage [44].…”
Section: Inhibition Off-target Activitymentioning
confidence: 99%
“…For instance, confining CRISPR technology-based perturbations to selected cell types in genetic studies in animals is critical, and ensuring specificity and hence safety in therapeutic genome editing in human patients is even more critical; thus, Acrs provide a new option to overcome these challenges based on Cas protein function. Hoffmann et al [106] developed a novel cell-type-specific Cas-ON switch based on AcrIIA4 and controlled by cellular miRNA signatures, confining spCas9 activity to hepatocytes or cardiomyocytes. In parallel with that work, Hirosawa et al constructed a synthetic mRNAdelivered Cas9-ON system using miRNA-responsive AcrIIA4 mRNA on the basis of improving the RNAbinding protein L7Ae-based miR-Cas9-ON switch they built previously [107,108].…”
Section: Potential Application Of Type II Anti-crispr Proteinsmentioning
confidence: 99%
“…In parallel with that work, Hirosawa et al constructed a synthetic mRNAdelivered Cas9-ON system using miRNA-responsive AcrIIA4 mRNA on the basis of improving the RNAbinding protein L7Ae-based miR-Cas9-ON switch they built previously [107,108]. Compared with a Cas-ON switch based on an L7Ae repressor, this Cas-ON switch design based on Acrs showed greater control than the previous system due to the high affinity of Acrs for Cas9-sgRNA complexes [106,107]. Furthermore, a subsequent study validated the efficiency of this Cas-ON switch based on Acrs by adeno-associated virus vectors delivered to adult mice, and the data showed that NmeCas9, along with an AcrIIC3 constructed that was targeted for repression by liver-specific miR-122, allowed editing in the liver while repressing editing in heart muscle, indicating that this strategy provides safeguards against off-tissue genome editing [109].…”
Section: Potential Application Of Type II Anti-crispr Proteinsmentioning
confidence: 99%